The built and urban heritage is an inexhaustible source of inspiration for the design of architectural works or urban compositions. - Hanafi, Abdelhakim; Alkama, Djamel; Sayad, Bouthaina (Journal of Architecture and environment of child, 2021)
Heritage is a materiel and immaterial wealth, for that it must be preserved and enhanced. Heritage is a real potential for development, and a means of satisfying a certain number of artistic, aesthetic and even leisure needs. It is therefore the source of several values of existence. The objective of this article is to see heritage as a source of inspiration in art, architecture, urban planning ... etc. seeing as it carries unlimited material and immaterial wealth. A reading and analysis on different inspiration profiles and different successful examples (architectural and urban) where designers have used heritage as a source of inspiration, in addition to what is inspired by heritage with all its types.